Long-Run Tax Incidence: A Comparative Dynamic Approach - Boadway, Robin (Review of Economic Studies, 1979)
Journal Article Long-run Tax Incidence: A Comparative Dynamic Approach Get access Robin Boadway Robin Boadway Queen's University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 46, Issue 3, July 1979, Pages 505–511, https://doi.org/10.2307/2297016 Published: 01 July 1979 Article history Received: 01 December 1977 Accepted: 01 October 1978 Published: 01 July 1979